Production Analysis and Fisheries Management of Spanish Mackerel (Scomberomorus spp.) in Bangka Belitung Islands Province, Indonesia - Sunita Priyani; Olifia Ratna Sari; Fadhilah Junia Putri; Iren Aprillia; Syahdan Akbar; Sudirman Adibrata (Coastal and Marine Journal, 2025)
Spanish mackerel (Scomberomorus spp.) is a pelagic fishery commodity with high economic value that is widely utilized in the Bangka Belitung Islands Province. High fishing activity has the potential to put pressure on the sustainability of fish resources if not balanced with proper management. Therefore, this study aims to analyze Spanish mackerel (Scomberomorus spp.) production, assess the utilization status of large pelagic fish resources, and describe fisheries management conditions in Bangka Belitung Islands Province. This study was conducted from April to May 2025 in Bangka Belitung Islands Province using secondary data obtained from the Statistics Data Portal of the Ministry of Marine Affairs and Fisheries and other relevant scientific publications. The research method used is a literature study and secondary data analysis obtained from the Ministry of Maritime Affairs and Fisheries Statistics Data Portal and various related scientific journals. Data were analyzed descriptively to determine the development of mackerel production and the condition of large pelagic fish resource utilization in the study area. The results show that mackerel production fluctuated with an increasing trend during the 2020–2024 period. The highest production occurred in 2024 at 17,149.72 tons, while the lowest production occurred in 2020 at 9,964.02 tons. Based on Ministerial Decree MMAF No. 19 of 2022, the utilization rate of large pelagic fish in the Indonesian Fisheries Management Area (IFMA) 711 is classified as fully exploited, with a utilization rate of 0.7. This condition indicates that intensive utilization of fish resources requires sustainable management through controlling fishing activities, monitoring fishing gear, and implementing measured fishing policies to maintain the sustainability of fish resources in the Bangka Belitung Islands Province.